Ni-polymer gels-derived hollow NiSb alloy confined in 3D interconnected carbon as superior sodium-ion battery anode. (10th April 2018) - Lin, Zhihua; Wang, Guanhua; Xiong, Xunhui; Zheng, Jie; Ou, Xing; Yang, Chenghao
Abstract: Antimony is being extensively investigated as anode material for sodium ion batteries (SIBs) due to its appropriate sodium insertion potentials, flat charge-discharge plateau and high sodium storage capacity. However, it suffers from unsatisfied cycling stability originated from the huge volume change during cycling. Herein, hollow NiSb spheres confined by three-dimensional interconnected carbon matrix (NiSb⊂3DCM) are prepared by a cross-linking reaction between Ni 2+ and alginate and a galvanic replacement reaction. Benefiting from its the hollow, porous structure and mechanical buffer provided by Ni and carbon coating, NiSb⊂3DCM electrode can deliver a stable capacity of 366 mAh g −1 with 94.3% capacity retention rate after 400 cycles operated at 1 A g −1, which is the best cycling performance reported so far for Sb-based alloy anodes. Graphical abstract: Hollow NiSb spheres confined by three-dimensional interconnected carbon matrix deliver an unprecedented cycle life with excellent capacity. Highlights: Hollow NiSb spheres confined by 3D interconnected carbon are prepared. A cross-linking reaction and a galvanic replacement reaction are proposed. As an anode for SIB, they show an unprecedented capacity retention rate. The performance is due to the hollow and Ni and carbon mechanical buffer.